Práticas pedagógicas de acesso à língua escrita e deficiência intelectual: um estudo em classe regular de ensino - Arantes, Luciana Nascimento Crescente (2021)
The present study aimed to analyze the teaching of written language to a student with intellectual disability, inserted in the regular education system of the Municipality of São Paulo, expressed by the pedagogical practice of a classroom teacher and by the support intern, through video recordings and records in a field notebook, which, after its transcription and organization, resulted in five scenes that sought to record in detail the actions aimed at developing her writing. The choice of the educational unit was due to the recognition that the Regional Board of Education is related to the pedagogical project developed, as well as that of the regent teacher for the quality of the pedagogical work carried out, as indicated by the pedagogical coordinator. Data analysis was supported by the contributions of Vigotski (2008), in particular, the pedagogical mediation of Soares (2009) regarding the social function of the writing system through the distinction between the domain of writing mechanics and its social use and Ferreiro (1991) with regard to writing as a representation system, in contrast to the perspective that considers it as a simple code of oral language. The main achievements can be summarized as follows: constant focus on formal elements of written language, to the detriment of its social use, for all students, with even greater restrictions in relation to the student with intellectual disabilities; pedagogical mediation processes with poor exploitation, which do not contribute to the effective constitution of readers and writers; in relation to students with intellectual disabilities, the huge reduction in the content presented reveals the perspective of the irreversibility of cognitive deficit, which results in the view of the impossibility of appropriating elementary levels of literacy